2021
DOI: 10.1016/j.redox.2021.101907
|View full text |Cite
|
Sign up to set email alerts
|

Divergent trajectories of cellular bioenergetics, intermediary metabolism and systemic redox status in survivors and non-survivors of critical illness

Abstract: Background Numerous pathologies result in multiple-organ failure, which is thought to be a direct consequence of compromised cellular bioenergetic status. Neither the nature of this phenotype nor its relevance to survival are well understood, limiting the efficacy of modern life-support. Methods To explore the hypothesis that survival from critical illness relates to changes in cellular bioenergetics, we combined assessment of mitochondrial respiration with metabolomic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 72 publications
0
19
0
1
Order By: Relevance
“…For instance, a previous study observed a rapid increase in extracellular free thiols following transient hypothermia-induced vasoconstriction in patients with primary Raynaud's phenomenon and systemic sclerosis [ 42 ]. Another example constitutes a study in which extracellular free thiols were observed to change dramatically over the course of several days in patients having critical illness [ 43 ]. These observations underscore the reversibility and dynamic nature of processes that are related to oxidative modification of extracellular free thiols, thereby lowering their total availability in the systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a previous study observed a rapid increase in extracellular free thiols following transient hypothermia-induced vasoconstriction in patients with primary Raynaud's phenomenon and systemic sclerosis [ 42 ]. Another example constitutes a study in which extracellular free thiols were observed to change dramatically over the course of several days in patients having critical illness [ 43 ]. These observations underscore the reversibility and dynamic nature of processes that are related to oxidative modification of extracellular free thiols, thereby lowering their total availability in the systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction and metabolic alterations are typically observed in patients with critical illness myopathy 66 . Suppression of fatty acid oxidation and NADH‐linked (mitochondrial complex I‐supported) respiration occur within days of admission to the ICU 67 . Sepsis triggers profound long‐lasting ultrastructural defects in skeletal muscle mitochondria 68,69 .…”
Section: Structure and Function Of The Neuromuscular System In Covid‐19mentioning
confidence: 99%
“…Recovery from critical illness is strongly associated with restoration of oxidative phosphorylation 67 and the activation of mitochondrial biogenesis, 70 with eventual survivors showing higher intramuscular ATP content than non‐survivors 69 . Low muscle mitochondrial content in ICU survivors contributes to long‐term weakness 73 .…”
Section: Structure and Function Of The Neuromuscular System In Covid‐19mentioning
confidence: 99%
“…These seemingly counterintuitive changes may be explained by the need for redox balance at the whole-body level. There is supportive evidence for this explanation in the literature, with demonstration of opposing changes in glutathione redox status within plasma and erythrocytes in critically ill patients [ 50 ] and in healthy individuals subjected to acute aerobic exercise [ 51 ]. Alternatively, the lower GSSG levels after exercise may be reflective of an increased capacity for reduction in skeletal muscle.…”
Section: Discussionmentioning
confidence: 94%